Factors affecting road traffic accidents in benghazi, libya - Ibrahim Al-Ghaweel; Saleh A Mursi; Joel P Jack; Irene Joel (Wolters Kluwer Medknow Publications, 2009)
Objectives: The aim of the study was to evaluate the factors responsible for road traffic accidents in Benghazi. Material and Methods: Retrospective and descriptive studies were done in the years 2006-2007. The data was collected from Traffic and License Department, Benghazi. The data were analyzed, based on fatalities, the severely handicapped, hit and run victims and were correlated with age, sex, time, environmental factors, type of roads, etc. Results: One-Thousand-Two-Hundred-Sixty-Five accidents occurred between the years 2006-2007 within the Benghazi city limits; 11.14% of the injuries were fatal; 67.35% of the victims had severe injuries and 21.51% escaped with minor injuries. [Table 1] shows that 73.04% lost their lives within the city limits, 13.47% on the fly-over, and 2.12% on minor roads connected to main roads within the city limits. The mean of the accidents and its standard deviation were 16.66± 25.67 with a variance of fatality of 1.54. Conclusion: It is concluded from the studies that major road traffic accidents occur because of environmental stress factors. In addition, fatalities and the seriousness of the accidents depend on a number of factors such as the age of the vehicle, safety measures, human error and time and place of accident.